Genetic prognostic factors for neoadjuvant chemoradiotherapy for colorectal cancer - V. A. Grigorenko; E. P. Kulikov; S. A. Mertsalov; Yu. D. Kaminsky; A. A. Nikiforov; A. I. Sudakov (Успехи молекулярной онкологии)
Introduction. There has been a recent trend toward a gradual increase in the incidence of rectal cancer and a decrease in the average age of patients. These changes interpret the need to personalize treatment in each case.Objective – to evaluate the association of polymorphic variants of some genes with the results of neoadjuvant chemoradiotherapy of rectal cancer.Materials and methods. We analyzed polymorphic variants of MTHFR, XPD, XRCC1, XRCC1, P53, VEGF, EGFR, TNF, CHEK2 and MMP1 genes in 76 patients with rectal cancer who underwent preoperative chemoradiation therapy followed by surgical treatment. Genotyping was performed by DNA isolation from venous blood leukocytes of the subjects followed by polymerase chain reaction with electrophoretic detection of the result.Results. Statistical analysis of the association of polymorphic variants of the studied genes with the treatment pathomorphosis revealed significance in relation to the MMP1-1607 gene (1G >2G) (p = 0.033). There was also an association of co-carrying polymorphic variants of TNF (G / A) + MMP1 (2G / 2G) genes with grade III–IV therapeutic pathomorphosis (p = 0.007).Conclusion. Carriage of recessive allele of MMP1 gene can be a predictor of favorable prognosis of preoperative chemoradiotherapy in patients with rectal cancer.